2023
DOI: 10.14202/vetworld.2023.168-174
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance of Escherichia coli from the milk of Ettawa crossbred dairy goats in Blitar Regency, East Java, Indonesia

Abstract: Background and Aim: Antimicrobial resistance, especially antibiotic resistance, is one of the most severe public health challenges. Antibiotic resistance occurs when bacteria avoid and fight the mechanism of action of antibiotic drugs. This study aimed to determine the resistance of Escherichia coli from the milk of Ettawa crossbreed dairy goat at Blitar Regency, East Java, Indonesia, with the antibiotics streptomycin, sulfonamides, and trimethoprim. Materials and Methods: A total of 34 milk samples of Ettawa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…E. coli contamination in products of animal origin is widespread. In Blitar Regency, East Java, contamination of E. coli was identified from a raw goat milk sample of 100% (34/34) (Agatha et al, 2023). In Surabaya, East Java, high microbial contamination was identified in chicken meat from local markets, namely S. aureus 58.3%, Salmonella spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…E. coli contamination in products of animal origin is widespread. In Blitar Regency, East Java, contamination of E. coli was identified from a raw goat milk sample of 100% (34/34) (Agatha et al, 2023). In Surabaya, East Java, high microbial contamination was identified in chicken meat from local markets, namely S. aureus 58.3%, Salmonella spp.…”
Section: Resultsmentioning
confidence: 99%
“…A positive test for the presence of E. coli was indicated by a metallic green colony (Figure 1). Then, followed by gram staining and biochemical tests, namely, the IMViC test, consisting of indole production test, methyl red (MR) test, Voges-Proskauer (VP) test, and citrate test (Agatha et al, 2023).…”
Section: Most Probable Number (Mpn) Methodsmentioning
confidence: 99%
“…Notably, the distribution of ESBL-encoding E. coli displays geographical variability, as substantiated by multiple research investigations conducted in various nations. Extensive evidence points to the identification of ESBL-producing E. coli in diverse contexts within the Indonesian settings, encompassing healthcare facilities [1], dairy farming establishments [1][2][3], and the surrounding ecological milieu [1]. These discerned occurrences emphasize the potential for interspecies transmission of ESBL-producing E. coli, thereby warranting heightened attention and investigation [1].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the incidence of AMR in animal health is increasing because of its involvement in diverse animal species and microbes, varying livestock environments, and intricate resistance mechanisms [11,12]. Previous studies have identified livestock, such as ruminants, as plausible reservoirs of antimicrobial-resistant bacteria and resistance genes, including Escherichia coli [13][14][15].…”
Section: Introductionmentioning
confidence: 99%